Uma Análise Sobre a Imagem da Dimensão Estrutural da Prática Pedagógica em Materiais Curriculares Educativos - Da Silva Prado, Airam; De Oliveira, Andréia Maria Pereira; Barbosa, Jonei Cerqueira [UNESP] (FapUNIFESP (SciELO), 2016)
In this paper, we presented an analysis of educational curriculum materials' texts through the sociology's lens of Basil Bernstein. The concept of classification, prepared by Bernstein, was used to analyze the relationship between discourses and relations between spaces that are expressed in the texts of the educational curriculum materials. In particular, we focused on educational curriculum materials about pedagogical practices in mathematics classes. The documental analysis, in a qualitative approach, was used in this study. The results show that such materials suggest, by mean of its texts, a dimming of the borders between the discourses and between the spaces that were used by subjects. Thus, the structural dimension of pedagogical practice was constituted in the educational curriculum materials about mathematical modeling by flexible images.
An analysis about the image of structural dimension of the pedagogical practice in educational curriculum materials
Keywords: Educational Curriculum Materials; Pedagogical Practice; Structural Dimension